If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4n + -1)(2n + 4) = 0 Reorder the terms: (-1 + 4n)(2n + 4) = 0 Reorder the terms: (-1 + 4n)(4 + 2n) = 0 Multiply (-1 + 4n) * (4 + 2n) (-1(4 + 2n) + 4n * (4 + 2n)) = 0 ((4 * -1 + 2n * -1) + 4n * (4 + 2n)) = 0 ((-4 + -2n) + 4n * (4 + 2n)) = 0 (-4 + -2n + (4 * 4n + 2n * 4n)) = 0 (-4 + -2n + (16n + 8n2)) = 0 Combine like terms: -2n + 16n = 14n (-4 + 14n + 8n2) = 0 Solving -4 + 14n + 8n2 = 0 Solving for variable 'n'. Factor out the Greatest Common Factor (GCF), '2'. 2(-2 + 7n + 4n2) = 0 Factor a trinomial. 2((-2 + -1n)(1 + -4n)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-2 + -1n)' equal to zero and attempt to solve: Simplifying -2 + -1n = 0 Solving -2 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1n = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1n = 0 + 2 -1n = 0 + 2 Combine like terms: 0 + 2 = 2 -1n = 2 Divide each side by '-1'. n = -2 Simplifying n = -2Subproblem 2
Set the factor '(1 + -4n)' equal to zero and attempt to solve: Simplifying 1 + -4n = 0 Solving 1 + -4n = 0 Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4n = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4n = 0 + -1 -4n = 0 + -1 Combine like terms: 0 + -1 = -1 -4n = -1 Divide each side by '-4'. n = 0.25 Simplifying n = 0.25Solution
n = {-2, 0.25}
| 4y+4=3y-6 | | 8x+3=13+3x | | (5a^2x+3ax^2-5x)+(2a^2x-5ax^2+7x)= | | 12x-10=62 | | -5(X+3)2(x-1)=-14 | | 8(2)+5= | | -9w-19=4w-6 | | -9-(4)(2)(x)=3249 | | 8x^2-21x+10=0 | | 8x^2-1x-9=0 | | 10w+16=10w+16 | | 3.2q-4.1-4.6q=-2.4q-3.2 | | 1+p+5+p=-2 | | 6r(2r-1)= | | 5x+24=12x+60 | | 6m+10=25-m | | 5x+11=12x+60 | | (5x^2-x-7)+(2x^2+3x+4)= | | 20e+50f=8(40) | | 22x-26x=10-14 | | -10-8x=-110+6 | | 3x-5y-4y+9x+2= | | 2xa-11=-5 | | 5x=48+2x | | (5x+3o)+9o= | | -3(4)+-2=x | | -(x-1)-4(x-3)=58 | | -0.2(-15x-10)=10 | | -7(4)+15=x | | z(2z-9)(z+4)=0 | | x^2+kx-9=0 | | 5=4(x-4)+3-3x |